RESOLUTION OF THE XVITH CONGRESS OF PEDIATRICIANS OF RUSSIA «ACTUAL PROBLEMS IN PEDIATRICS» - A.A. Author ("Paediatrician" Publishers LLC, 2009)
(Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(3):142-146)